The Role of the Colombian State in the Formation of the Steel Industry in Boyacá. 1930-1980 - Barreto Bernal, Patricia Carolina; Jurado Jurado, Juan Carlos (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This study presents the role of the Colombian State in the formation of the steel industry in the department of Boyacá, between 1933 and 1980. The interventionism of the Colombian State has been a fundamental element for import substitution, which may be explained by the endogenous and exogenous conditions of the national economy during World War II (1939-1945). We start from the hypotesis that the State is a political form which has adopted the capitalist economic system; for this reason State interventionism in economy is a characteristic of the process of modernization experienced in Colombia between the end of the XIX century and the beginning of the XXth. We take into account the state policies and laws regarding the steel industry, the State institutions and trade unions that developed this sector, the decline of interventionism, and the emergence of the private steel companies. Secondary sources consulted were national press, the official trade union journal between 1960 and 1970, and CONPES (the Colombian Council of Social and Economic Policies).Lastly, we emphasize certain key points that are beyond the limits of the present study, such as interrelation between the steel industry and other sectors and knowledge areas, and the national and international technologies required for the activaton of great industries; vital ideas that may generate new research processes.